The Dynamics of Horticultural Farmers Groups in Malang Regency and Batu City - Ary Bakhtiar; Rahmad Pulung Sudibyo; Indriani Indriani; Wahid Muhammad Shodiq (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The development in the agricultural sector required an increase in human resource capacity. The special effort can be in the form of training and skills in processing agricultural products. The research aim was to analyze the factors that influence the dynamics of horticultural farmers groups, and assessed the level of group dynamics and the independence of horticultural farmer group members. The determination of the location of the research was performed by using a qualitative descriptive method, which was performed in two locations, which were Pujon Sub-district, Malang Regency and Batu City. The research was conducted from October to November 2019. The analysis used was descriptive analysis to describe the level of group dynamics in the two regions which were Pujon Sub-district Malang Regency and Batu City. The dynamics level of horticultural farmers in each region was categorized as low (? 20%), moderate (20.1% - 40%), normal (40.1% - 60%), high (60.1% - 80.00 %) and very high (? 80%). The results showed that the dynamics value of the horticultural group in Malang City was included in the high category, which was 77.18%. While the value of group dynamics in Malang Sub-district of Pujon was 77.08% and in Batu City was 77.27%, both regions were included in the high category.